Pengembangan Media Pembelajaran Interaktif berbasis PowerPoint Materi Mitigasi Bencana Kebakaran Hutan dan Lahan - Cahyani, Meiza Ilka; Aprilian, Azahria Nurfadhilah; Putri, Diffa Rahmani (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2024)
Forest and land fires often occur, especially in peat areas such as in Riau province. It is necessary to build students' knowledge of the importance of forest and land fire disaster mitigation. Therefore, this study aims to develop interactive learning media based on PowePoint on forest and land fire disaster mitigation material. The research method uses a research and development approach with the ADDIE model. The products resulting from this development were tested with elementary school students. The results of this study indicate that interactive media based on PowerPoint on forest and land fire disaster mitigation material is very appropriate for use in learning in elementary schools.